Study of an adaptive energy harvesting system for high voltage piezoelectric generators. (27th July 2018) - Li, Po; Xu, Dazheng; Chen, Fu; Guan, Mingjie
Abstract: An adaptive energy harvesting system for high voltage piezoelectric generators is presented in this paper. Maximum power point tracking scheme is applied in the adaptive system. Low-power-consumption schemes are applied in the control system and harvesting circuit. A self-startup circuit is also applied to the system. Theoretical analysis was explored to determine optimal parameters for the harvesting system. Experiments were done to verify the theoretical analysis. The experimental results show that the harvesting system can achieve an efficiency of 17.5 ∼ 73.3% for piezoelectric generator with a peak open-circuit voltage of 6 ∼ 20 V. And the harvesting system can be self-powered from low input power as 25 μW. The average power consumption of the microcontroller can be low as 3.5 μW.